Influences, Learning Styles and Learning Preferences of Learners in Special Program in Foreign Language in Korean - El Chamberlain Abellana; Losel Mae Abellana (Journal of Research in Education and Pedagogy, 2025)
The study explored the dominant learning styles, influential factors, and preferred learning activities and media of Grade 7 students enrolled in the Korean language program, aiming to enhance instructional material design and teaching strategies. Adopting a one-group descriptive research design, the study involved a total population of 80 students. A purposive sampling procedure was used in selecting the respondents. The study covered the scope within the second semester of the school year 2021-2022. Data collection employed two main instruments: Fleming’s VARK model, which identifies learning styles (Visual, Auditory, Read/Write, and Kinesthetic), and a 20-item questionnaire adapted from Ancho (2019) to identify learning preferences. Results were analyzed using frequency, percentage, and mean. The findings reveal that the majority of respondents were visual learners, favoring activities that included reading and writing dialogues as well as the use of comic strips. These preferences suggest that visually engaging and text-rich materials are particularly effective in facilitating language acquisition. Additionally, factors such as cultural interest and relevance of Korean pop culture emerged as significant motivators for learning the language. The study underscores the importance of tailoring instructional materials to align with students’ dominant learning styles and preferences. By incorporating visually stimulating and interactive media, educators can enhance engagement and improve learning outcomes. These insights provide valuable input for curriculum development, particularly in designing activity sheets and pedagogical approaches that resonate with learners’ needs and interests.